Understanding the symptoms and sources of variability in second language sentence processing. Issue 4 (26th September 2016) - GABRIELE, ALISON; FIORENTINO, ROBERT; COVEY, LAUREN
Abstract : Cunnings (2016 ) proposes that differences between native (L1) and second language (L2) sentence processing can best be explained in terms of susceptibility to effects of interference and an overreliance on discourse level cues during memory retrieval. Cunnings' argument that difficulty in retrieval operations may provide a better explanation than a syntactic deficit account for explaining certain L1-L2 differences is convincing. However, the proposal for the 'overuse' of discourse is too broad and needs to be refined in terms of the specific contexts and conditions under which learners have difficulty. We also believe that difficulty with cue-based retrieval is still a characterization of the symptoms of differences between L1-L2 processing, and does not necessarily address the source of the variability.